Clinical outcome and analysis of radical prostatectomy in clinical stage B and C prostate cancer - Miyoshi, Y (Hinyokika kiyo. Acta urologica Japonica, 2001)
Between 1989 and 1999, 40 patients treated with radical prostatectomy for clinical stage B and C prostate cancer were analyzed. Prostate-specific antigen (PSA) failure after radical prostatectomy occurred in four patients, and one of them died of clinical recurrence of prostate cancer. Cause-specific survival at 5 years was 91.7% and PSA failure-free rate at 5 years was 76.8%. Staging accuracy of CT and MRI image was not satisfactory. In 41.7% patients, extracapsular extension can not be determined. Preoperative serum PSA levels of pathologically organ-confined disease (OCD) patients were significantly lower than those of pathologically non-OCD patients. Further analysis indicated that preoperative serum PSA levels of greater than 20.1 ng/ml are useful predictors for pathologically non-OCD